Profitabilitas, Likuiditas, Senioritas Direktur Utama Dan Tax Avoidance Dengan Ukuran Perusahaan Sebagai Variabel Moderasi - Pusposari, Devy; Dewi, I Gst. A. A. Sintya Purnama (KRISNA: Kumpulan Riset Akuntansi, 2024)
Taxes are obligatory contributions owed by a taxable person or corporate taxpayer to the state. Taxation is one of the burdens for companies that can reduce their profits. Therefore, the company will make an effort to be able to efficiently reduce the corporate tax burden. One of the efforts that the company can make is tax avoidance. This research is aimed at finding out the effect of profitability, liquidity, and seniority of the president of the board on tax avoidance with firm size as a moderation variable. Sampling in this study uses purposive sampling techniques. In this study, there were 7 property and real estate companies and 35 samples. The data used in this study is obtained from secondary data that uses data from the financial statements of property and real estate companies listed on the Indonesian Stock Exchange in 2018–2022. The results of this study show that partially profitability has no effect on tax avoidance, while liquidity and seniority of the president of the board have a negative and significant effect on tax avoidance. Simultaneously, profitability, liquidity, and seniority of the president of the board have an effect on tax avoidance. The firm size moderation variable is unable to moderate the effect of profitability on tax avoidance, the effect of liquidity on tax avoidance, and the effect of the seniority of the president of the board on tax avoidance.